Detection of hyaluronic acid in the aquatic waste and extraction by enzyme technology - Bac, Vo Hoai; Hong, Tran Thi; Mai Phuong, Nguyen Thi; Truong, Le Van (Academia Journal of Biology, 2016)
Hyaluronic acid (HA) is a linear polysaccharide composed of a repeating disaccharide unit of β(1-4) glucuronic acid and β(1-3) N-acetylglucosamine. HA is present in tissues as cartilage, skin, rooster combs, umbilical cord, vitreous humour and sinovial fluid. In recent years, an increasing interest has been reported due to its numerous applications as cosmetic and pharmaceutical compound. HA levels from Carcharhinus sorrah, Dasyatis kuhlii and Pangasius bocourti lived in the sea area of Vietnam were the first time investigated. The extract of hyaluronic acid was dialyzed and digested with ENV enzyme. The optimal conditions of ENV protease for hydrolyzing cartilage and skin were determined as follows Carcharhinus sorrah: 1.25 IU enzyme/30gram of cartilage, 18 h, pH 6,0 at 60oC; Dasyatis kuhlii: 1.50 IU enzyme/30gram of cartilage, 30 h, pH 6,0 at 65oC and Pangasius bocourti: 1.50 IU enzyme /1.5gram of skin, 30 h, pH 6,0 at 65oC).